Geologia da ocorrência de ouro orogênico de Reriutaba, Ceará, Brasil - Sampaio, Caio Cesar Fernandes Teixeira de (2019)
Processing and interpretation of airborne geophysics data and remote sensing images,petrography and geochemistry were applied to support the study of an orogenic goldmineralization located in the Ceará Central Domain of the Borborema Province, in theReriutaba city, Ceará state. From the gamma-spectrometric images, ten distinct gamma-spectrometric domains were identified in the study area, corresponding to sevenlithostratigraphic units: 1) Canindé Unit of the Ceará Group; 2) Independência Unit of theCeará Group; 3) Brasilianos Granites (São José Granite and Lombo Granite); 4) Post-Orogenic Granite with associated Basic-Intermediate Volcanism (Varjota Granite); 5) IpuFormation of the Serra Grande Group of the Parnáiba Basin; 6) Eluvial Deposit; 7) AlluvialDeposits. Based on the images K/eTh, Factor F and Anomalous Potassium, areas withpotassium hydrothermal alterations were identified. Based on the magnetometric images, fivedifferent magnetometric domains and magnetometric lineaments were observed, mostly fromNE-SW direction, which helped in the lithostructural interpretation of the study region. Fromthe AMF and AS images, amphibolites with magnetite were identified in the Canindé Unitand it was possible to better delimit the basic-intermediate volcanic rocks with magnetiteassociated with Varjota Granite. The highest OIF calculated RGB composition 752 elaboratedfrom the Landsat-8/OLI multispectral images allowed to improve the lithostratigraphicinterpretation performed according to the gamma-spectrometric images. ALOS/PALSARimages were topographically modeled using the shaded relief technique to improve thestructural interpretation made supported by the magnetometric images. In addition to thedominant structural trend NE-SW, which corresponds to shear zones and foliations, two othertrends of NNE-SSW and E-W directions, which represent faults related to shear zones, wereidentified. The Reriutaba orogenic gold mineralization is located in the Ceará Central Domainof the Borborema Province. The mineralization is hosted in the amphibolite faciesmetavolcanossedimentary rocks of the Canindé Unit of the Ceará Group, which is composedby migmatites, amphibolites, calcissilicatic rocks and schist in the study area. Themineralization was formed in second and/or third order faults of the Reriutaba Shear Zone,where due the percolation of hydrothermal fluids were filled by mineralized quartz veins andhydrothermally altered the brecciated wallrocks to mineralized breccias. There are two stylesof mineralization: 1) gold/electrum and gold-bearing sulfides disseminated in quartz veins and(2) gold/electrum and gold-bearing sulfides disseminated in quartz-carbonate breccias.Although occurs hosted in amphibolite facies metamorphic rocks, the formation of the mineralization is associated with a low temperature hydrothermal metamorphism that affectedthe metavolcanossedimentary rocks of the Canindé Unit of the Borborema Province duringthe late stages of Brasiliano Orogeny. Pyrite, galena, sphalerite, arsenopyrite, chalcopyrite andbornite are the dominant ores minerals commonly associated the mineralization. Molybdeniteand bismuthinite may be present as accessories. Scapolite, albite, k-feldspar, biotite,muscovite, epidote, chlorite, sericite, quartz, sulfides, kaolinite and barite are generally thehydrothermal alteration minerals related with the mineralization. Tourmaline, actinolite,tremolite, calcite and ankerite are others hydrothermal alteration minerals that also occurs inthe study area. Chemical analysis of the mineralized hydrothermal breccias indicate that thehost rocks of the mineralization were enriched in Si and depleted in Ca, Mg, Na, P and Tiduring the hydrothermal alterations. The mineralization have a unique element associationconstituted by Au, Ag, Fe, Pb, Zn, As and Cu, and are depleted in Sb, Te and W.Concentrations from about 1 to 30 ppm of Au and 4 to 85 ppm of Ag are present in themineralized hydrothermal breccias.